DESAIN DAN ANALISIS NUMERIK RUANG BAKAR BRIKET SAMPAH ANORGANIK UNTUK PENGAPLIKASIAN PADA MIKROTURBIN GAS - Erlanda A Pane; Eko Prasetyo; Rudi Hermawan; David H Gouwin (Rekayasa Mesin, 2022)
The utilization of briquettes as a source of electricity generation is still low due to the briquette characteristics that have high moisture content. This research analyzes the briquette's potential as a source of electrical energy by utilizing its syngas with microturbine gas. The high quality of syngas can be reached by the optimal combustion chamber design. Therefore, the research aim is to be able to design the optimum combustion chamber for the briquette combustion process to generate the syngas. This research method uses two steps, i.e., the design of the combustion chamber and numerical analysis of the briquette combustion process through Computational Fluid Dynamics (CFD) simulations. Numerical analysis of the combustion process using three types of briquettes with different inorganic waste compositions, i.e., K1 type, K2 type, and K3 type. The research results explain the optimum design of the combustion chamber with a total length dimension of 220 mm, an inlet fuel section, and combustion chamber-syngas pipeline diameter of 50 mm and 75 mm, respectively. In addition, the dimensions of the primary air holes are 7 mm, and the secondary air holes are 5 mm. Type K1 briquettes are capable of producing syngas (kg/s) consisting of 6.9x10-13 CO, 3.04x10-31 H2, and  1.8x10-20 CH4. That syngas composition includes in the criteria of syngas in the microturbines gas that produce electric power of 2.3-2.5 kW. The conclusions explain that the combustion chamber can be added to the microturbine gas component, and K1 type briquette can be a solid fuel.